Modelling Delta-Notch perturbations during zebrafish somitogenesis - Murray, P; Maini, P; Baker, R (2013)
The discovery over the last 15 years of molecular clocks and gradients in the pre-somitic mesoderm of numerous vertebrate species has added significant weight to Cooke and Zeeman's 'clock and wavefront' model of somitogenesis, in which a travelling wavefront determines the spatial position of somite formation and the somitogenesis clock controls periodicity (Cooke and Zeeman, 1976). However, recent high-throughput measurements of spatiotemporal patterns of gene expression in different zebrafish mutant backgrounds allow further quantitative evaluation of the clock and wavefront hypothesis. In this study we describe how our recently proposed model, in which oscillator coupling drives the propagation of an emergent wavefront, can be used to provide mechanistic and testable explanations for the following observed phenomena in zebrafish embryos: (a) the variation in somite measurements across a number of zebrafish mutants; (b) the delayed formation of somites and the formation of 'salt and pepper' patterns of gene expression upon disruption of oscillator coupling; and (c) spatial correlations in the 'salt and pepper' patterns in Delta-Notch mutants. In light of our results, we propose a number of plausible experiments that could be used to further test the model. © 2012 Elsevier Inc.